Massification in Higher Education Institutions in Africa: Causes, Consequences and Responses - Mohamedbhai, Goolam (International Journal of African Higher Education, 2014)
Most public higher education institutions in Africa, in response to historical conditions, have enrolled students in excess of their capacity, resulting in massification and negative consequences on educational quality. Increased enrolment has addressed issues of equity; but the equally important issue of ensuring equity in success for the enrolled students has received limited attention. Apparently graduation rates in higher education in Africa remain fairly low. Higher education institutions have taken several corrective measures to address the consequences of massification. Governments have also created new institutions and put quality assurance systems in place. There have also been continental responses. Sub-Saharan Africa has the lowest tertiary enrolment of any world region, a handicap in its development. It must also meet the demands of its rapidly increasing secondary school graduates. There is a compelling need to further increase tertiary enrolment, a situation that challenges both institutions and countries. The growth in private higher education, if regulated and quality-controlled, could relieve this pressure. Pour des raisons historiques, la majorité des établissements d’enseignement supérieur d’Afrique admet plus d’étudiants qu’elle ne peut en accueillir. Ceci conduit à la massification de l’enseignement supérieur et a des conséquences négatives sur sa qualité. L’augmentation de la participation a permis de répondre à des problèmes d’équité, mais la tout aussi importante question de l’équité dans la réussite des étudiants admis a reçu une attention limitée. Le taux de réussite dans l’enseignement supérieur en Afrique reste faible. Les établissements d’enseignement supérieur ont mis en place plusieurs mesures visant à corriger les conséquences néfastes de la massification. Les gouvernements ont aussi créé de nouvelles institutions et mis en place des systèmes d’assurance qualité. Des réponses ont par ailleurs été proposées à l’échelle du continent. Cependant, l’Afrique sub-saharienne a le plus faible taux d’inscription dans l’enseignement supérieur du monde, un handicap pour son développement. Elle doit aussi répondre aux demandes d’une population de diplômés du secondaire qui augmente rapidement. Il est impossible de nier la nécessité d’augmenter les admissions dans l’enseignement supérieur, une situation qui pose des problèmes aussi bien aux établissements qu’aux nations. La croissance des établissements privés pourrait permettre de relâcher la pression, s’ils sont correctement régulés et contrôlés en termes de qualité.